Recent Advances in Thermal Management Techniques for High-Performance PMSMs - A Comprehensive review - Azom, Md Ali; Khan, Md Yakub Ali (Control Systems and Optimization Letters, 2025)
This paper presents recent advancements in thermal management techniques for high-performance permanent magnet synchronous motors (PMSMs), highlighting their role in improving efficiency and reliability. Due to their high-power density, small size, and exceptional efficiency, permanent magnet synchronous motors, or PMSMs, have become indispensable in high-performance applications like industrial automation, electric cars, and aerospace. Since excessive heat generation can lower motor efficiency, shorten its lifespan, and jeopardize dependability, the growing demands for improved performance have created serious issues in thermal management. The latest developments in thermal management strategies for high-performance PMSMs are thoroughly examined in this paper. Important thermal issues are covered, such as the development of hot spots, unequal heat distribution, and thermal resistance at crucial contacts. The incorporation of cutting-edge cooling technologies into motor design is examined in this research, along with liquid cooling, heat pipes, phase change materials, and enhanced thermal interface materials. Furthermore, it is emphasized how important computational thermal modeling and simulation are to maximizing PMSM thermal performance. The interaction of mechanical, thermal, and electrical dynamics is emphasized to provide dependable and effective motor operation. This review identifies current limitations and explores future trends, including adaptive cooling techniques and AI-driven thermal modeling, to enhance PMSM efficiency and sustainability. This will allow for further breakthroughs in sustainable and energy-efficient technologies.